(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
The study aims to identifying the economic and social characteristics of Shami goat breeders in the Jableh region. And to identify the most important problems facing them. To achieve the objectives of the study, the descriptive and analytical approach was relied on, data were collected by questionnaire private study the reality of Shami goat breeders . (45) questionnaires were distributed on Breeders in villages belonging to the region of Jablah. The results showed that (66.7%) hold a preparatory certificate, and (42.2%) of the studied sample raise Shami goats for the purpose of producing milk. The most important reasons for choosing this project is that the Shami goats give a high production rate of (73.33%), and (42.2%) of them obtained the heads of the Shami goats according to government grants. And Shami goat breeders in the studied area agreed that the problems they suffer from lie in securing the fodder and securing vaccines, in addition to the low prices of goat milk and its products. It was also noticed that (64.4%) of respondents sell their production directly to the consumer.